Tree monocultures in a biodiversity hotspot : impact of pine plantations on mammal and bird assemblages in the Atlantic Forest - Iezzi, María Eugenia (2018)
Fil: Iezzi, María Eugenia. Universidad Nacional de Misiones. Instituto de Biología Subtropical; Argentina.